Delays Impair Learning and Can Drive Convergence to Inefficient Strategies - Rahmandad, Hazhir; Gary, Michael Shayne (Organization Science, 2023)
With so many possible choices, why do managers adopt the strategies they do? We identify delays between adopting a strategy and observing the full implications of that choice as a critical factor influencing strategic choices. Using a simulation of a service firm, we conduct two behavioral experiments to investigate how delays interact with outcome uncertainty to shape learning, strategy adaptation, and performance outcomes. Two mechanisms emerge from how different subject groups perceive, react to, and learn in the presence of delayed feedback and uncertainty. First, when multiple viable strategies exist, longer delays lead both general participants and experienced managers toward alternatives that have rapid returns. When those alternatives are suboptimal, delays may strengthen convergence to inefficient strategies. Second, delays and uncertainty may also induce learners to persist with their a priori strategies. Managers show larger confidence in their priors and thus underperform general participants when the underlying task structure diverges from those priors. Both mechanisms can undermine performance. Moreover, delays and uncertainty may reduce heterogeneity in strategies and performance in more dynamic, uncertain environments, leading to convergence as tasks grow more complex and where decision makers possess similar priors. History: This paper has been accepted for the Organization Science Special Issue on Experiments in Organizational Theory. Funding: Funding from the Massachusetts Institute of Technology and UNSW Business School supported this research. Supplemental Material: The online appendices are available at https://doi.org/10.1287/orsc.2020.1405 .